2018
DOI: 10.1063/1.5042478
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for indirectly driven double shell capsules

Abstract: Double shell capsules are predicted to ignite and burn at relatively low temperature (∼3 keV) via volume ignition and are a potential low-convergence path to substantial α-heating and possibly ignition at the National Ignition Facility. Double shells consist of a dense, high-Z pusher, which first shock heats and then performs work due to changes in pressure and volume (PdV work) on deuterium-tritium gas, bringing the entire fuel volume to high pressure thermonuclear conditions near implosion stagnation. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Possible experiments on inter-atomic Kα emissions. Experimental verification of these first-principles predictions of interatomic Kα emissions can possibly be conducted at the Omega Laser Facility utilizing the platform of double-shell implosions 14,15,42,43 . In a double-shell target, the inner metal shell can be made of mid-Z Fe-Cu or Fe-Zn alloys with a core of D2-gas fill.…”
Section: Density Dependence Of Interspecies Radiative Transition (Irt)mentioning
confidence: 95%
See 1 more Smart Citation
“…Possible experiments on inter-atomic Kα emissions. Experimental verification of these first-principles predictions of interatomic Kα emissions can possibly be conducted at the Omega Laser Facility utilizing the platform of double-shell implosions 14,15,42,43 . In a double-shell target, the inner metal shell can be made of mid-Z Fe-Cu or Fe-Zn alloys with a core of D2-gas fill.…”
Section: Density Dependence Of Interspecies Radiative Transition (Irt)mentioning
confidence: 95%
“…When a low-Z outer shell (beryllium or polystyrene) is driven symmetrically by the 60-beam OMEGA laser to spherically impact on the inner shell, it can cause the inner Fe-Zn (or Fe-Cu) shell to implode. A small convergence ratio of C R = R initial /R final ∼8-10 of the metal shell could give rise to a mass density of ρ = 500 to 2000 g cm −3 for the inner Fe-Zn (or Fe-Cu) shell at its stagnation 42,43 . To create the 1s holes of Fe and Zn/Cu ions, one option is to use the high-intensity OMEGA EP beam to generate MeV electrons that can remove some of the 1s electrons of Fe and Zn/Cu ions through collisions.…”
Section: Density Dependence Of Interspecies Radiative Transition (Irt)mentioning
confidence: 99%
“…It was found that the interface coupling effect, the distorted transmitted shock and the geometric constraint greatly affect the development of instability. However, the problem of a light gas layer accelerated by a converging shock has not yet been well investigated -which is more relevant to the so-called double-shell implosion (Montgomery et al 2018). This motivates the current study.…”
Section: Introductionmentioning
confidence: 99%
“…This ignition scheme, which has dominated inertial confinement fusion (ICF) for decades, has yet to produce ignition in the laboratory, primarily due to the effects of asymmetry and mix 3,4 . Ignition schemes that abandon the propagating burn wave concept and instead aim to ignite the fuel volume simultaneously have recently gained interest, with Revolver 5 and Double Shell targets 6,7 being the prime examples.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, higher implosion velocity is not necessarily a benefit. Although faster implosions could reduce the convergence required to reach ignition, the fuel would be less compressed and susceptible to premature disassembly 5,6 . For the Revolver design, a pusher implosion velocity of u I = 19 cm/µs results in a required pusher convergence ratio of 9.4.…”
Section: Introductionmentioning
confidence: 99%